SESSILE ORGANISMS COLONISATION ON CONCRETE SUBSTRATE “CRYPTO” AT DIFFERENT DEPTH IN THE PATCH REEF OF PRAMUKA ISLAND - Genadi Algadri; Beginer Subhan; Dondy Arafat; Ahmad Taufik Ghozali; Prakas Santoso; Hawis Madduppa (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Acceleration of the process of recovery of damaged reefs require rehabilitation, management and supervision of well-planned and sustainable. One of the rehabilitation process is to create artificial reef. This study aims to look at the rate of attachment of sessile organisms on cement media called “crypto”. A total of 270 cement media at each shelf. The size of cement media is 5x5x1 cm. The cement media were deployed at a depth of 6 meters and 10 meters. The rate of attachment of sessile organisms was compared between the upper and lower of the media side at each depth and between depths. Different organisms was observed colonized concrete media such as shells, sponges, worms, green algae, red algae, and brown algae. Percentage of coverage of sessile biota at a depth of 6 meters was significantly higher than 10 meters. Percentage of coverage of sponges at a depth of 6 meters and 10 meters, showed no significantly different (P = 0.0670). The other sessile biota, value of the test results showed significant differences between depths, such as the brown algae (P< 0.0001), red algae (P = 0.0003), and green algae (P = 0.0022). The type succession occurs in this research was likely a primary succession. Keywords: sessile biota, biodiversity, rehabilitation, concrete block, colonization, succession